Characterisation of a novel transcript LNPPS acting as tumour suppressor in bladder cancer via PDCD5‐mediated p53 degradation blockage - Li, Juan; Wang, Yifan; Zhang, Xinya; Yang, Xuemei; Qi, Qiuchen; Mi, Qi; Feng, Maoxiao; Wang, Yunshan; Wang, Chuanxin; Li, Peilong; Du, Lutao (Clinical and translational medicine, 2023)
Background Long non‐coding RNAs (lncRNAs) play a crucial role in tumour initiation and progression. However, little is known about their contributions to p53‐related bladder cancer (BC) inhibition. Methods By using high‐throughput sequencing, we screened the expression profiles of lncRNAs in BC and adjacent non‐tumour tissues. The roles of a novel lncRNA, named LNPPS [a lncRNA for programmed cell death 5 (PDCD5) and p53 stability], were determined by gain‐ and loss‐of‐function assays. RNA pull‐down followed by mass spectrometry analysis, RNA immunoprecipitation assays and other immunoprecipitation assays were performed to reveal the interactions among LNPPS, PDCD5 and p53, and the regulatory effect of LNPPS on the complex ubiquitination network comprising PDCD5, p53 and mouse double minute 2 homologue (MDM2). Results LNPPS was downregulated in BC and markedly inhibited the viability of BC cells by inducing PDCD5/p53‐related apoptosis in vivo and in vitro. Mechanistically, LNPPS, serving as a scaffold, connected PDCD5 and p53 with nucleotides (nt) located at 121‒251 nt and 251‒306 nt of LNPPS, respectively. This process allowed LNPPS to protect PDCD5 from proteasomal degradation by blocking its K20 site ubiquitination. On the other hand, the increased interaction between PDCD5 and p53 displaced p53 from the MDM2‒p53 ubiquitination complex, resulting in an increase in p53 expression and related apoptosis levels. Moreover, LNPPS could induce the accumulation of PDCD5 and p53 in the nucleus and exert a synergistic effect on the prevention of protein degradation. In addition, we confirmed that the downregulation of LNPPS in BC was mediated by the decreased N6‐methyladenosine (m6A) modification. Conclusion Our findings highlight a novel cross‐talk between LNPPS and the PDCD5/p53/MDM2 ubiquitination axis in BC development, indicating its potential as a therapeutic target for BC patients. 1. A novel m6A‐regulated lncRNA LNPPS played a suppressive role in BC development. 2. LNPPS, a novel PDCD5‐interacting partner, protected PDCD5 from proteasome degradation by masking its K20 site ubiquitination. 3. LNPPS acted as a scaffold to connect PDCD5 with p53, impairing MDM2‐mediated p53 ubiquitinationb.